The Role Of Telkomsel Public Relations In Maintaining Customer Loyalty Through Telkomsel Poin Program) - Putri Maretta Gultom; Anis Endang; Sri Narti (Universitas Dehasen Bengkulu, 2026)
This study examines the role of Telkomsel Public Relations (PR), particularly within the Retention and Loyalty Operation (RLO) Division, in maintaining customer loyalty through the Telkomsel Poin partnership program in Bengkulu City. The problem addressed in this research is how PR activities contribute to sustaining customer loyalty in a competitive telecommunications industry. The aim of this study is to analyze the implementation of PR roles in supporting the Telkomsel Poin program as a customer retention strategy. The research employs a qualitative descriptive method, using in-depth interviews, observation, and documentation. Informants include the Supervisor and Staff of the RLO Division, two Telkomsel Poin customers, and a partner merchant (Solaria Restaurant). The findings indicate that PR performs four main roles: communication technician, expert prescriber, communication facilitator, and problem-solving facilitator. These roles are reflected in the preparation of program communication materials, selection of strategic partners aligned with customer needs, facilitation of two-way communication between customers and partners, and assistance in resolving customer complaints during point redemption. The study concludes that the PR role significantly contributes to maintaining customer loyalty by encouraging repeated participation and strengthening long-term relationships.